Impact of Remote Equatorial Winds and Local Mesoscale Eddies on the Existence of "River in the Sea" Along the East Coast of India Inferred From Satellite SMAP. Issue 12 (7th December 2020) - Suneel, V.; Alex, M. J.; Antony, Thomas P.; Gurumoorthi, K.; Trinadha Rao, V.; Harikrishnan, S.; Gopalakrishna, V. V.; Rama Rao, E. P.
Abstract: The Northern Bay of Bengal (NBOB) exhibits extreme salinity stratification caused by intense summer monsoon rainfall and associated river discharge. This accumulated fresh water plume in NBOB is believed to be transported along the East coast of India (ECI) by East India Coastal Current (EICC), known as River in the Sea (RIS). Though in situ sea Surface Salinity (SSS) measurements are sparse, the advancement of satellite monitoring system has provided a unique opportunity to unravel salient features of RIS. In the present study, in situ SSS at five selected regions around the Indian coast and open ocean are utilized to validate the Soil Moisture Active Passive (SMAP) (L3, v4.3) products. Further, this new SMAP data is used to examine year‐to‐year variability of RIS during 2015–2019 and the driving forces responsible for its existence. This SMAP SSS exhibited 1.52, 0.46, 0.38, 1.45 RMSD and 0.97, 0.82, 0.85, 0.86 correlation in NBOB1, NBOB2, Central BOB (CBOB) and Western BOB (WBOB), respectively with in situ measurements. This data also depicted the presence of "RIS" all along the ECI only during November in consistent with the magnitude of Kelvin wave induced EICC. The southward extension of RIS along the ECI is primarily based on the magnitude of remote equatorial wind induced forces. The mesoscale eddies in south‐western BOB (SWBOB) alters the shape of RIS and even inhibit its southward propagation completely. Plain Language Summary: Satellite monitoring of sea surface salinity (SSS) in the recent decade has provided a unique opportunity to study its variability associated with ocean atmosphere interactions. However, its accuracy especially near coastal regions is a challenging task. The advanced version of a satellite Soil Moisture Active Passive (SMAP) SSS products (v4.3) were validated with Bay of Bengal in situ salinity data in particular near coastal and fresh water dominant regions. This new SSS products perform very well even near shore regions and was able to capture southward propagation of freshening signal also known as "River in the Sea (RIS)" along the East coast of India. Utilizing this advanced SSS products, the interannual variability of RIS and the driving forces responsible for its variability are studied. Our analysis indicated that the southward propagation of RIS is primarily based on the magnitude of remote equatorial wind induced forcing in addition to the Indian Ocean Dipole associated forcing. Additionally, presence of mesoscale eddies in the south‐western Bay of Bengal can interrupt and even restrict its southward propagation of "RIS." Key Points: The new Soil Moisture Active Passive (SMAP) v4.3 sea surface salinity (SSS) products were validated over Bay of Bengal (BOB) emphasizing near coastal and fresh water dominant regions The southward propagation of River in the Sea (RIS), and its interannual variability is altered by remote equatorial wind induced forces Eddies in southwestern BOB modulate RIS and also restrict its southward propagation completely